An Evaluation of the Mechanisms of Galacto-Oligosaccharide (GOS)-Induced IgE Cross-Linking on Basophils in GOS Allergy. - Lee, Li Yuan Gabriella Nadine (Frontiers Media SA, 2022)
10.3389/falgy.2022.840454